Food preferences of guanaco (Lama guanicoe cacsilensis) and its competence with cattle in the Calipuy National Reserve, Peru - Linares, Luis (2010)
The objective of this research was to determine the degree of food competition between guanaco and livestock in Calipuy National Reserve. Vegetation cover (CV) was determined by a survey of vegetation and composition of diets using a micro histological technique of feces (50 guanacos, 35 cows and 25 horses). The dietary overlap was determined by Horn Index (I), food preferences by Ivlev index (E) and the diet diversity by Shannon-Weaver index (D) .We found a low - moderate food competition between the guanaco and the cattle and horses. The dietary overlap was greater during the rainy season (I=0.80 and 0.88) where forage supply was high (CV=63%) and lower during the dry season (R=0.58 and 0.64) when there were shortages of food (CV=50%). The guanaco was an intermediate selective consumer. The dietary diversity of adults increased during the dry season (D=0.62, p<0.01) including up to 70% of herbs and shrubs, showing a high flexibility in food between seasons (I=0.64) and habitats (I=0.75, p<0.01), which allowed it to minimize competition with cattle and horses, which consumed mainly grasses in both seasons (>60%) and did not show the same flexibility (I=0.90, p<0.01). Chulengos and juveniles were more sensitive to seasonal variations, its consuming a lower percentage of shrubs, but had a strong preference for small herbs.